2023
DOI: 10.1039/d3ra00398a
|View full text |Cite|
|
Sign up to set email alerts
|

Preparation of UV-curable PSAs by grafting isocyanate-terminated photoreactive monomers and the effect of the functionality of grafted monomers on the debonding properties on Si wafers

Abstract: Photoreactive pressure-sensitive adhesives (PSAs) were prepared by grafting mono- or difunctional photoreactive monomers onto acrylic PSA, and their adhesion properties were evaluated before and after UV curing for application as dicing tape.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It was reported that the viscoelastic PFPE residue remained after the UV curing process. [30][31][32][33] The viscoelastic PFPE residue remaining on the surface of the stencil can improve the filter efficiency by promoting adhesion force between particles and the surface and preventing particle bounce-off. As illustrated in Figure 5, it is confirmed that a greater amount of particles was captured to the PFPE stencil surface compared to the PUA stencils, in the same face velocity, spacing between polymeric stencils, and stacking configuration.…”
Section: The Pfpe Polymeric Stencils For Enhanced Filter Efficiencymentioning
confidence: 99%
“…It was reported that the viscoelastic PFPE residue remained after the UV curing process. [30][31][32][33] The viscoelastic PFPE residue remaining on the surface of the stencil can improve the filter efficiency by promoting adhesion force between particles and the surface and preventing particle bounce-off. As illustrated in Figure 5, it is confirmed that a greater amount of particles was captured to the PFPE stencil surface compared to the PUA stencils, in the same face velocity, spacing between polymeric stencils, and stacking configuration.…”
Section: The Pfpe Polymeric Stencils For Enhanced Filter Efficiencymentioning
confidence: 99%